(untitled) (Libellarium: journal for research in the field of information and related sciences, 2011)
The aim of the paper is to analyze and contextualize book trade advertising in Zadar periodicals in the early 19th century. The corpus consists of Kraljski Dalmatin, the first newspaper published in the Croatian language, and Zora dalmatinska, published during the Revival period entirely in Croatian. The advertisements found in the corpus were recorded, classified and analyzed, and the more interesting ones are discussed in the text. Research results indicate that the first newspaper published in Croatian, Kraljski Dalmatin, was used for occasional and modest book trade advertising - seven ads were found in all issues of this paper. 30 years later, Zora dalmatinska was used more frequently for different forms of book trade advertising. 93 examples found in thepaper advertise books, newspapers, calendars and almanacs, calls for subscription, reminders for overdue books and late returns, book reviews, etc. Two basic conclusions can be drawn from research results. Firstly, the publishers of the first newspapers published in Zadar grasped quickly the advertising potential of this type of media, which became a widely accepted means of communication in the early 19th century. Secondly, newspaper advertising reflected the current cultural and political circumstances, which is illustrated by frequent ads for the Revival works in book tradeZora dalmatinska.